2018
DOI: 10.15614/ijpp.v9i01.11743
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, self-compassion, mindfulness and emotional well-being of doctors

Abstract: The present study was conducted to explore the relationship between resilience self-compassion, mindfulness and emotional well-being of doctors working in critical and non-critical care units of patients. It was hypothesized that there is likely to be positive relationship between resilience, self-compassion, mindfulness and emotional wellbeing of doctors and resilience, self-compassion and mindfulness are likely to be positive predictors of emotional well-being of doctors working in critical care and non crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
5
1
1
Order By: Relevance
“…Supporting the results of this study Sabir et al (2018), showed that resilience is a factor that is positively related to positive affect on emotional well-being and negatively related to the negative effect of emotional well-being. As a psychological factor, resilience can play a role in an individual's ability to maintain a positive sense of wellbeing even during times of stress.…”
Section: Discussionsupporting
confidence: 88%
“…Supporting the results of this study Sabir et al (2018), showed that resilience is a factor that is positively related to positive affect on emotional well-being and negatively related to the negative effect of emotional well-being. As a psychological factor, resilience can play a role in an individual's ability to maintain a positive sense of wellbeing even during times of stress.…”
Section: Discussionsupporting
confidence: 88%
“…However, even before the pandemic, it has been reported that female residents demonstrated poorer wellness compared with male residents [ 9 ]. This is also found to be true outside of the medical workforce [ 12 ]. It is suggested that the poorer wellness scores in women seem are due to decreased self-compassion and focus on basic needs—which relies on feelings of autonomy, ability and competence, and the connection of professional relationships [ 13 ].…”
Section: Discussionmentioning
confidence: 93%
“…For example, an intervention that increased MA in emergency medical personnel has been shown to reduce burnout and improve compassion satisfaction (Ducar et al, 2020). Furthermore, MA has been associated with resilience among doctors in critical care units (Sabir et al, 2018). However, these studies did not evaluate the independent effects of both distress tolerance and MA within the same model.…”
Section: Discussionmentioning
confidence: 99%
“…A mindfulness-based intervention that improved MA was also associated with reductions in perceived stress and burnout and improvements in compassion satisfaction among emergency medical personnel (Ducar et al, 2020). Moreover, MA has been cross-sectionally associated with greater resilience and positive affect among doctors in critical care units (Sabir et al, 2018). Taken together, results from previous research suggest that MA protects against psychological symptoms and also improves occupational health (e.g., reduces burnout; increases compassion satisfaction) and resilience among first responders and similar helping professionals.…”
mentioning
confidence: 99%